Priority Based Data Transmission for WBAN - Jay Manalastas Ventura; Arnel Fajardo; Ruji Medina (Institute of Advanced Engineering and Science, 2019)
Wireless Body Area Sensor Network (WBASN) or Wireless Body Area Network (WBAN) is a growing field in healthcare applications. It enables remote monitoring of patient’s physiological data through wireless communication. It is composed of sensor network which collects physiological data from the patient. There are several issues concerning WBAN such as security, power, routing protocol to address QoS metrics (reliability, end-to-end delay, and energy efficiency), etc. The focus of the study is the issue on different QoS metrics. There were several QoS aware routing protocol that has been proposed which implements multiple queues for different types of data. However, one issue on multiple queue system is starvation, end-to-end delay, and reliability. The study proposed an efficient priority queue based data transmission that improves the end-to-end delay, reliability, and queuing delay of QoS aware routing protocol.